CD4+/CD25+ T cells suppress autologous CD4+/CD25− lymphocytes and secrete granzyme B during acute and chronic hepatitis C. Issue 2 (11th August 2014) - Perrella, Alessandro; D'Antonio, Anna; Sbreglia, Costanza; Sorrentino, Paolo; Conca, Paolo; Atripaldi, Luigi; Conti, Pio; Perrella, Oreste
Abstract We aimed to verify whether CD4+/CD25+ T cells suppress CD4+ T cells and secrete Granzyme B (GZB) during acute and chronic hepatitis C (CHC) infection. We enrolled 50 subjects: 20 patients with CHC (Group A), 15 healthy individuals (Group B), 10 patients with acute hepatitis C later evolved to persistent infection (Group C) and five patients who resolved hepatitis C virus infection during acute phase (Group D). We analysed, on enrolled subjects CD4+/CD25+ T cells and related GZB production as well as Annexin V activity. Patients from Groups A and C had higher frequency and function of peripheral Treg cells than healthy individuals. Groups A and C showed an increase in spot‐forming colonies (SFCs) of GZB compared with Group B (P < 0.01, Mann–Whitney U‐test). CD4+/CD25+ T cells in Group D had a lower number of GZB SFCs compared with Groups A and C but higher number than Group B (P < 0.01 Mann–Whitney U‐test). Annexin V production was higher in Groups A and C than B or D. Patients having acute and chronic hepatitis C have a higher Treg frequency and function in peripheral blood than healthy controls or those resolving the infection in acute phase secreting GZB, probably inducing apoptosis.